TEACHING READING BY USING WFR (WARMING-UP FOR READING) TO INCREASE READING SKILL - Afifah Linda Sari; Radityo Tri Nugroho (Universitas Lambung Mangkurat, 2018)
Abstract: This research is aimed at describing the implementation of teaching reading by using WFR, to describe the problems of using WFR in teaching reading and to know the students’ response of the implementation of WFR. The result of this study is intended to give contribution to the teaching and learning English. The research was done to the second year students of SMP N 5 Banjarbaru. As the sample, the researcher took 40 students of IIA class. The data were collected through observation, interview and test. After collecting the data and analyzing them and describing the result of them by action research procedure, the researcher described the result of the research. The WFR was conducted in four meetings. It is appropriate in teaching reading and helps the students increasing/developing their reading skill. There are some problems faced by the students in teaching learning process: in which most of students have difficulties in arranging the sentence correctly, the students have difficulties in translating the word from English into Indonesian and Indonesian into English, the students do not understand the instruction of the worksheet, and the students have difficulties in finding the main idea of the text. During the teaching learning process from the first meeting until fourth meeting the response of the students is good. They were enthusiastic in every meeting. Evidently, the result of the hypothesis testing showed that the t- observation is always greater than the t-table; in degree of freedom N - 1 = 39 and level of significance 0,05. It means that there is a significant difference of the students’ achievement before and after the implementation of WFR. The conclusion is the teaching reading using WFR to the second year students of SMP N 5 Banjarbaru yields a good result. WFR is appropriate method in increasing the students reading skills and helpful in teaching-learning process.